New-onset complement-mediated thrombotic microangiopathy during the COVID-19 pandemic - Christof Aigner; Martina Gaggl; Sophie Schmidt; Renate Kain; Nicolas Kozakowski; André Oszwald; Zoltán Prohászka; Raute Sunder-Plassmann; Alice Schmidt; Gere Sunder-Plassmann (Kidney & Blood Pressure Research)
Introduction: The coronavirus disease-19 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The virus is alleged to enable a proinflammatory state, that leads to the activation of the coagulation and the complement cascade. In this study, we aimed to establish the impact of the COVID-19 pandemic on patients with new onset of cTMA/aHUS in the Vienna TMA cohort and whether COVID-19 or SARS-CoV-2 vaccinations would pose a greater risk of initial manifestation of cTMA/aHUS. Methods: We used the Vienna TMA cohort database to examine the prevalence of COVID-19 related and of SARS-CoV-2 vaccination-related aHUS/cTMA during the first 3 years of the COVID-19 pandemic in a large single-center cohort. Results: Between March 2020 and May 2023, a total of 7 patients experienced their first aHUS/cTMA episode. No patient experienced a TMA relapse or more than one episode during the follow-up period. Three TMA episodes were attributable to either COVID-19 (n=1; 33%) or SARS-CoV-2 vaccination (n=2; 66%), respectively. All three patients had systemic signs of TMA and TMA was confirmed by kidney biopsy in all cases. Among the seven patients we recorded five infections that triggered one TMA episode (20%) and 19 vaccinations triggered two TMA episodes (10%; p=0.52, odds ratio 0.47; 95% CI 0.04-8.39). Conclusion: We speculate, that both SARS-CoV-2 vaccinations and COVID-19 episodes can represent a triggering factor for aHUS/cTMA episodes in (genetically) vulnerable individuals. However, COVID-19 might have a stronger association and might be a stronger trigger than the SARS-CoV-2 vaccines. The incidence of new aHUS cases did not differ from the pre-pandemic era in a large tertiary care centre cohort.